Detecting food authenticity and integrity. Issue 16 (13th April 2016) - Ellis, David I.; Goodacre, Royston
Abstract : Welcome to this joint Analyst and Analytical Methods themed collection on detecting food authenticity and integrity. Our Guest Editors for the collection, David I. Ellis and Royston Goodacre, discuss the work showcased.